FUNCTIONAL OUTCOME OF SURGERY IN PATIENTS WITH ACETABULAR FRACTURES - Khan, Shaukat Hayat; Ara, Iffat; Raza, Shahbaz; Sipra, Sarfraz (Journal of Ayub Medical College Abbottabad, 2013)
Background: High velocity injuries due to road traffic accidents can be managed conservatively or surgically depending whether the fracture is displaced or not. The objective of this study was to evaluate functional outcome of surgery in patients of acetabular fractures. Methods: It was a case series study conducted in Department of Orthopaedic Surgery, Pakistan Institute of Medical Sciences from 1st october 2007 to 15th December 2008. Thirty patients were included in the study fulfilling the inclusion criteria. Patients were followed up in the OPD and were evaluated for functional outcome by using Harris Hip Scoring System. Results: Total 30 patients were operated during the study period. Mean age of patients was 33.5 years. Males were 22 and females were 8. Twenty-three patients had road traffic accident as a cause of injury and 7 were due to fall. Ninety-three percent of patients were operated within 2 weeks. Most common type of fracture was both column fractures. In only one patient sciatic nerve injury was present postoperatively. Average hospital stay was 7 days. Out of 30 patients, 21 patients were classified to have good score, 4 patients were classified to have excellent score while 5 patients were having poor result. Conclusion: The surgical management of displaced acetabular fractures yields good results. Keywords: Acetabular fractures, Harris hip score, judet views, Road traffic accidents, outcome